Chemical speciation of some heavy metals and human health risk assessment in soil around two municipal dumpsites in Sagamu, Ogun state, Nigeria. Issue 1 (1st October 2016) - Ogunbanjo, Oriyomi; Onawumi, Oluwayemi; Gbadamosi, Muideen; Ogunlana, Adejoke; Anselm, Oluwaseun
Abstract: Environmental and health risk posed by heavy metals from municipal landfill cannot be over emphasized. However, the toxicity and fate of metal in the soil is dependent on its chemical form and therefore quantification of the different forms of metal is more meaningful than the estimation of its total concentration. This study investigated the chemical form and potential hazards of heavy metal pollution at two municipal landfills in Sagamu, Ogun state, Nigeria. Soil samples were collected around the landfills and chemical form of Cu, Zn, Cd, Pb, and Fe were studied, using the Tessier Five-step sequential chemical extraction procedure. The results showed that Cu and Fe were speciated into residual fractions with averages of 23.9 and 31.3% respectively, while Cd and Zn were associated with Carbonate fractions with respective averages of 20.3 and 20.6%. The order of mobility and bioavailability of these metals are: Cd > Pb > Cu > Zn > Fe. A comparison of the result of total extractible metals with standard set by USEPA reveals that Cd and Cu level in the dumpsite soils are far above the critical permissible limit of 3.0 and 250 mg kg −1, respectively which potent a health risk. Assessment of soil pollution level using geoaccumulation index ( I geo ) revealed that the landfill was extremely polluted by Cd ( I geo  > 5). Pearson correlation and principal component analysis showed that there were no significant correlations ( p  < 0.05) among all the metals, suggesting that they are all from different anthropogenic sources. The cancer risk ranged from 1.36E−01 to 2.18E−04 and 5.82E−01 to 9.35E−04 for Children and Adult respectively. The level of cancer risk falls above the threshold values (10 −4 –10 −6 ) which US Environmental Protection Agency considered as unacceptable risk. Based on the above findings, it was suggested that environmental management policy should be implemented to decrease the environmental risks.